2012
DOI: 10.1111/j.1365-2044.2012.07149.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium sulphate on postoperative coagulation, measured by rotational thromboelastometry (ROTEM®)*

Abstract: SummaryWe investigated the effects of magnesium sulphate on blood coagulation profiles using rotational thromboelastometry in gynaecological patients undergoing pelviscopic surgery. Patients were randomly allocated to the magnesium group (n = 20) or control group (n = 20). The magnesium group received magnesium sulphate (50 mg.kg )1 followed by continuous infusion of 15 mg.kg), whereas the control group received the same volume of isotonic saline according to the same methods. Mean (SD) postoperative serum mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
19
1
1
Order By: Relevance
“…Secondary outcomes were haemoglobin concentration, haematocrit, platelet count, PT‐INR and aPTT. The primary variable used for the power calculation was MCF based on the results of a previous study . Assuming a 40% difference in median values and a power of 80% with a risk of 0.025 for type‐1 errors, 10 patients needed to be studied.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcomes were haemoglobin concentration, haematocrit, platelet count, PT‐INR and aPTT. The primary variable used for the power calculation was MCF based on the results of a previous study . Assuming a 40% difference in median values and a power of 80% with a risk of 0.025 for type‐1 errors, 10 patients needed to be studied.…”
Section: Methodsmentioning
confidence: 99%
“…2---4 O magnésio é um medicamento usado para essa finalidade e seus efeitos positivos no controle do sangramento pós-operatório foram claramente definidos. 5,6 O magnésio é um antagonista do receptor N-metil-D--aspartato (NMDA) que diminui a necessidade de analgésicos e sedativos. Dexmedetomidina também é um agonista alfa-2 com propriedades sedativas, amnésicas e analgésicas.…”
Section: Introductionunclassified
“…Magnesium salts alone or mixed with other minerals and vitamins are commonly used as dietary supplements. Also, magnesium is infused intra-operatively in a variety of surgeries [2]. Magnesium is considered safe and beneficial [3][4][5][6], however there are some reports on its health risk when overdosed [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they revealed an interesting fact that in Germany during and shortly after the Second World War, magnesium sulfate was DOI: 10.5114/ceji.2013.35203 widely used as a muscle relaxant and the blood of patients examined post mortem after such treatment was unclottable [14]. Na et al investigated intra-operative infusion of magnesium sulfate by maintaining magnesium levels at the upper limit of the normal range (1.58 mmol/l) and found that Mg 2+ extends the clotting time [2]. Sekiya et al reported that not only Ca 2+ cations, but also Mg 2+ cations stabilize the native conformation of coagulation factor IX and at physiological concentrations significantly amplify the biological activities of this factor.…”
Section: Introductionmentioning
confidence: 99%